MANAJEMEN PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 KEMTUK GRESI KABUPATEN JAYAPURA - Ihongdem, Rosalina; Risamasu, Putri Ellen Gracia; Sembiring, Desy Anita Karolina (NOKEN : Jurnal Pengelolaan Pendidikan, 2021)
This study aimed to describe the learning management of Bahasa Indonesia at SMA Negeri 1 Kemtuk Gresi. This research method was qualitative research, with descriptive method. Data collection techniques were conducted with interview techniques, observations, and documentation studies. The sources of this research were principals, Bahasa Indonesia teachers, deputy principals of curriculum and students. The data analysis techniques used were by data reduction, data presentation and conclusion drawing. The results showed that (1) Planning of Bahasa Indonesia learning at SMA Negeri 1 Kemtuk Gresi was conducted by teachers of Bahasa Indonesia well, namely by preparing learning tools such as RPP, syllabus, semester programs and annual programs, (2) Organizing Bahasa Indonesia learning was done by dividing the theme or subject matter of each lesson material that would be presented in accordance with the time set by using the method of assignment, discussions, and lectures, (3) The implementation of Bahasa Indonesia learning was conducted in a structured manner in accordance with the learning tools or RPP, starting from the initial activities, core activities and final activities and (4) Evaluation of Bahasa Indonesia learning was carried out at a time when the learning process had not taken place with the pre-test, formative test and summative test assessment procedure.Keywords: Bahasa Indonesia; Learning; Management